THROMBOLYTIC THERAPY IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - E. V. Konstantinova; A. V. Magnitskyi; N. A. Schostak (Столичная издательская компания, 2016)
It is reported that the implementation in clinical practice thrombolytic (fibrinolytic) therapy resulted inmortality reduction during firstmonth after myocardial infarction from 17-18% to 5-8%. Different details of this therapy are considered: terms of thrombolysis since the beginning of myocardial infarction, alternative methods of coronary blood flow recovery , indications and contraindications, complications and side effects, estimation of thrombolysis efficacy. Fibrin-selective and fibrin-non-selective drugs are presented. Different fibrinolytics are described: streptokinase, anistreplase, alteplase, reteplase, tenekteplase. The results of large randomized clinical trials devoted to fibrinolytic therapy of myocardial infarction are analyzed: GISSI, ISSIS, TIMI, GUSTO, INJECT, ASSENT. The possibility to increase in efficacy and safety of fibrinolytics by their combination with acetylsalicylic acid, IIb/IIIa receptor inhibitors and heparins are discussed.